Physical Education-Professional And Pedagogical Features Of Oratory Skills In Sports Activities - Azimjon Ruziev (Euro Asian Journal Publishing, 2024)
in this work, the author studied the professional-pedagogical features of oratory skills in physical education-sports activities. The communication between the student and the teacher is revealed to be logical, psychological and spiritual. A lot in the lecture is illuminated by examples of the fact that it depends on the effectiveness of pedagogical communication.
Keywords: speech; speaker; skill; profession